Relationship between eating out frequency and taste preferences among urban adult residents - YANG Yunqi; LI Zizi; LIU Shuang; ZHANG Qin; YOU Jie; FANG Min; WU Rangpeng; JIA Xiaofang; LI Min; WANG Huijun; DU Wenwen; SU Chang (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveThis study aimed to investigate the association between eating out frequency and taste preferences among urban Chinese adults.MethodsA convenient sampling method was employed to select 1 957 adult residents aged 18 to 65 from four urban areas with complete survey data on eating out frequency and taste preferences. The study analyzed the current patterns of eating out and taste preferences and used a multifactor logistic regression model to assess the correlation between eating out frequency and taste preferences.ResultsThe study found that 35.8% of participants ate out less than once a week， 33.5% ate out 1-3 times a week， 18.3% ate out 4-6 times a week， and 12.4% ate out seven or more times a week. Gender differences were observed in taste preferences， with men having significantly higher rates of salty and oily taste preferences compared to women， while women had a higher preference rate of sweet taste. After controlling for relevant confounding factors， urban female residents who ate out 1-3 times a week had a 59% increased risk of salty taste preference （OR = 1.59） compared to those who ate out less than once a week. Similarly， urban female residents who ate out 1-3 times a week， 4-6 times a week， and seven or more times a week had an increased risk of sweet taste preference by 51% （OR = 1.51）， 71% （OR = 1.71）， and 77% （OR = 1.77）， respectively. Moreover， urban female residents who ate out 1-3 times a week and seven or more times a week had an increased risk of spicy taste preference by 54% （OR = 1.54） and 78% （OR = 1.78）， respectively. Compared with urban male residents who ate out less than one time a week， urban male residents who ate out 4-6 times a week have an increased risk of oily and spicy tastes by 61% （OR=1.61） and 85% （OR=1.85）， respectively.ConclusionThe study suggests that the frequency of eating out among urban residents may be associated with their taste preferences. Therefore， there is a need to enhance nutrition education and awareness to encourage the development of healthier eating habits.